Teacher, peer, and family support is associated with compliance behavior in consuming blood supplement tablets - Yusriani Yusriani; Harismawati Bahtiar; Fairus Prihatin Idris; Andi Asrina; Haeruddin Haeruddin; Nur Ulmy Mahmud (Journal of Midwifery and Nursing, 2023)
The prevalence of anemia in young women aged 15-24 years in Indonesia reaches 23.9%. Anemia occurs at all stages of human life and is more likely to occur in young women, one of which is female students. Compliance with iron supplement consumption is a form of behavior to prevent and treat anemia so the tendency of young women to adhere to regular blood supplement consumption can be analyzed using a behavioral theory, namely the Theory of Planned Behavior (TPB). This study aims to determine the relationship and influence of peer information support, teacher information support, and family information support on adherence to blood supplement consumption among female students at Al-Ikhlas Islamic Boarding School Ujung Bone in 2023. This research is a quantitative study using a cross study design. sectional. The statistical test used is chi-square. The research instrument was a structured questionnaire sheet, with a sample of 120 female students. The results showed that there was a statistically significant relationship between peer information support, teacher information support, and family information support on adherence to blood supplement consumption among female students at Al-Ikhlas Islamic Boarding School Ujung Bone in 2023.